Literature Study on The Use of Virtual Reality As A Digital-Based Learning Medium In BIPA Learning - Nurjanah, Elen; Poernomo, Kharisma Novia (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
In this digital era, teachers are required to be able to utilize technology-based learning media. One of the technology-based learning media is virtual reality. Virtual Reality (VR) is a technology that allows users to interact with digitally created and simulated environments that resemble the real world. The approach in this study uses literature studies. Literature studies are conducted by collecting references consisting of several previous studies and then compiled to draw conclusions. The results of the literature review were used to determine the potential use of virtual reality as a BIPA learning medium. The purpose of this study is to describe the role of virtual reality as a learning medium and describe the use of virtual reality in BIPA learning. The result of this study is that virtual reality has many roles as a learning medium and virtual reality can be used as an alternative learning medium in BIPA learning.